Analysis of the Role of Women in Development in Indonesia - Dike Maylina Widyanawati; Siti Aisyah (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2025)
This study aims to analyze the impact of female labor force participation rate (FLFPR), women’s representation in parliament (WRP), gender development index (GDI), women in professional employment (WPE), and fertility rate (FTR) on economic growth across Indonesian provinces, as measured by Gross Domestic Product (GDP) from 2019 to 2023. Drawing on human capital theory and gender economics, this research is grounded in the premise that gender inclusion enhances economic performance through broader talent utilization, higher productivity, and more equitable policy outcomes. The selected variables represent key dimensions through which gender equality can influence growth, labor participation, and professional employment, indicating women's direct economic contributions, political representation reflects institutional inclusivity, GDI captures structural gender disparities, and fertility rate reflects demographic and labor trade-offs. Using a panel data regression approach, the findings show that only FLFPR has a significant positive effect on GDP, highlighting the critical role of women's workforce participation in driving inclusive development. In contrast, WRP, GDI, WPE, and FTR do not exhibit statistically significant effects. These results underscore the importance of facilitating women's access to economic opportunities as a strategic pathway to enhance regional economic growth.